Pengaruh Kualitas Pelayanan, Persepsi Harga dan Nilai Pelanggan terhadap Loyalitas Konsumen melalui Kepuasan Pelanggan sebagai Variabel Intervening (Universitas Negeri Semarang, 2015)
This study aimed to determine the effect of service quality, price perception and customer value on customer loyalty through customer satisfaction as an intervening variable of the consumer-Indosat IM3 cellular card. Data were collected from 100 respondents of IM3 users using accidental sampling method, then processed using SPSS 16.0 software using path analysis. The results show that there is a positive and significant impact service quality, price perception and customer value to customer loyalty. Service quality has significant positive effect on loyalty through customer satisfaction as mediation, price perception and customer value has negatively affect loyalty through customer satisfaction as mediation